Value-added spent coffee grounds to produce caffeinated soap - รักษาพรต, สุพัตรา; สุวรรณเจริญ, สุนิษา; สว่างแก้ว, เรืองวิทย์; สามารถ, เกศสุดา; บุญเฒ่า, จิตรลดา (KKU Science Journal, 2018)
This research is aimed at the quantitative analysis of caffeine in the spent coffee ground in order to investigate the simple process to add the value of the spent coffee ground. Arabica and Robusta spent coffee from the coffee shop in Muang district, Chantaburi province were extracted by Soxhlet extraction using four different solvents including water, ethanol, ethyl acetate and dichloromethane at the boiling point of each solvent for 6 hours. The amount of the extracted caffeine was determined by high performance liquid chromatography (HPLC). It was found that dichloromethane gave the maximum extraction efficiency followed by ethyl acetate, ethanol and water, respectively. The maximum yields obtained from dichloromethane for both Arabica and Robusta are 0.27 and 0.21, respectively. As the extracted caffeine in the spent coffee ground is trace concentration, therefore it is not economical worth to extract the caffeine. Then the researchers produced caffeinated soap from the spent coffee ground. After the caffeinated soaps were stored for 15 days, the pH and the amount of foam were not significant different from the control soap. This study shows that the production of caffeinated soaps can not only added value to the spent coffee ground but also provide an alternative way for waste management.